Quantitation of proteins in silver stained polyacrylamide gels - Yuksel, K.O.; Gracy, R.W.
This study investigates some of the problems encountered in quantitation of proteins in silver stained polyacrylamide gels. Subunit molecular weight, isoelectric point and amino acid content are examined as possible factors for differential staining intensities of proteins. We also describe a procedure for quantitation using atomic absorption spectroscopy, independent of the colors formed upon silver staining. Using this method we show that some proteins such as pepsin bind silver but fail to develop visual color reactions.
Keywords: POLYACRYLAMIDE GEL; PROTEIN